Effect of drought on biomass allocation in two invasive and two native grass species dominating the mixed‐grass prairie. (6th December 2012) - Dong, X.; Patton, J.; Wang, G.; Nyren, P.; Peterson, P.
Abstract Control of exotic plant species invading the native prairie relies on our understanding of the eco‐physiological mechanisms responsible for the spread of these species as they compete with native plants for soil resources. We used a greenhouse pot experiment to study vegetative biomass allocation in response to drought stress in two exotic grass species, Kentucky bluegrass (Poa pratensis L.) and smooth brome (Bromus inermis Leyss), and two native species, western wheatgrass (Pascopyrum smithii (Rydb.) A. Löve) and green needlegrass (Stipa viridula Trin.). The experiment was conducted over 3 months in 2010 and again in 2011 in a factorial design of four species and two drought treatments. The proportional data of biomass allocation to shoots, roots, rhizomes and crowns (shoot base) of grass seedlings were analysed by both the nonparametric Mann–Whitney U‐test on the original data and one‐way anova on the arcsine‐transformed data. Our data suggest a clear distinction between the two invasive and two native species in potential competitiveness in soil resource use, with the two exotic species having higher biomass allocation to roots than the two native species and the native species having a higher biomass allocation to crowns than the two exotic species. It is interesting to note that the strongly rhizomatous smooth brome did not produce rhizomes in the first season's growth, regardless of the water stress level. The effect of drought stress on biomass allocation manifested itself more on rhizomes or crowns than on roots or shoots of the four studied grass species, with the effects species‐specific in nature.